2015
DOI: 10.1097/mnm.0000000000000271
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the diagnostic performance of H/M ratio between early and delayed phases for Lewy body disease

Abstract: ObjectivesThe aim of the study was to compare the diagnostic performance of early-phase 123I-metaiodobenzylguanidine (MIBG) scintigraphy with that of delayed-phase imaging in Lewy body disease (LBD).MethodsA retrospective cohort study of 123I-MIBG scintigraphy was carried out in 192 patients who were suspected of having LBD. Clinical diagnosis was obtained using the UK Parkinson’s Disease Brain Bank Criteria in some cases or the third report of the Dementia with Lewy bodies Consortium in others. The participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 14 publications
(22 reference statements)
0
12
0
Order By: Relevance
“…In 27 PD patients and 9 PSP patients, DAT-SPECT using 123 I-2β-carbomethoxy-3β(4-iodo-phenyl) tropane ( 123 I-β-CIT) and 123 I-metaiodobenzylguanidine (MIBG) scintigraphy were also performed as part of the clinical assessment. The heart to mediastinum (H/M) ratio in the late phase of MIBG scintigraphy used to confirm the diagnosis of PD ( Maruyama et al, 2015 ) and the specific binding ratio (SBR) of DAT-SPECT averaged across the bilateral basal ganglia (average SBR) were included as clinical covariates in the multiple regression analysis below. The typical clinical features for patient inclusion are summarized in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…In 27 PD patients and 9 PSP patients, DAT-SPECT using 123 I-2β-carbomethoxy-3β(4-iodo-phenyl) tropane ( 123 I-β-CIT) and 123 I-metaiodobenzylguanidine (MIBG) scintigraphy were also performed as part of the clinical assessment. The heart to mediastinum (H/M) ratio in the late phase of MIBG scintigraphy used to confirm the diagnosis of PD ( Maruyama et al, 2015 ) and the specific binding ratio (SBR) of DAT-SPECT averaged across the bilateral basal ganglia (average SBR) were included as clinical covariates in the multiple regression analysis below. The typical clinical features for patient inclusion are summarized in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] The amount of free radio iodide is the most important radiochemical impurity and must be limited to prevent excessive thyroid uptake. The amount of free iodide should be \1%-2% of total radioactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Insufficient evidence to conclude that delayed imaging has better accuracy than early imaging does not prove that there is no difference in accuracy. One of the studies provides weak evidence, rather than no evidence, for delayed imaging being more accurate (area under the curve 0.871 early, 0.893 delayed; P = 0.091) [ 9 ]. These three studies were quite large with 453, 111 and 192 cases included.…”
Section: Discussionmentioning
confidence: 99%
“…Three recent cardiac mIBG studies in Lewy body disease carried out by separate groups [8–10] have demonstrated no significant difference between diagnostic accuracy of early or delayed imaging, suggesting that early images alone could be sufficient. Acquiring early images alone would benefit both patients and clinical departments and would also make the test much more convenient than [ 123 I] 2β-carbomethoxy-3β-(4-iodophenyl)-N-(3-fluoropropyl) nortropane (FP-CIT), which requires a 3–6 h uptake period before scanning.…”
Section: Introductionmentioning
confidence: 99%